(untitled) (Journal of Architectural Design, 2022)
The article discusses the construction of many caravanserais in the IX-XVIII centuries as a result of the growth of cities in Central Asia, the Middle East and the growth of caravan trade, the history, activities and modern use of caravanserais built in the Middle Ages.